Characteristics of reciprocating speed of a low power consumption 4 K G-M cryocooler. Issue 1 (1st May 2022) - Masuyama, S; Kamiya, K; Numazawa, T
Abstract: This study is aiming to develop a low power consumption 4 K G-M cryocooler. As a first step, a two-stage G-M cryocooler with a 2 kW class compressor has been tested. The base model of cold head of two-stage G-M cryocooler is RDK-305D (Sumitomo Heavy Industries). We modified its second stage regenerator materials by filling magnetic materials Gd2 O2 S and HoCu2 spheres. An air-cooled compressor of SA115 (ULVAC CRYOGENICS) that rated input is 1.9 kW at 60 Hz was connected to the cold head. The experimental results showed that the cooling capacity of the second stage of 0.5 W at 4.2 K and the first stage of 25 W at 45 K was achieved with the cold head reciprocating speed of 48 rpm and the compressor electrical input of 2.09 kW. The relative Carnot efficiency of 1.7% at 4.2 K was calculated from the result. A low reciprocating speed of 48 rpm was chosen is to secure the sufficient expansion work in the second expansion space. This is considered an effective method to obtain a large cooling capacity at 4 K by low power compressor.